Alterações na qualidade do camarão de água doce Macrobrachium rosenbergii durante estocagem em gelo - Kirschnik, Peter Gaberz; Viegas, Elisabete Maria Macedo (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2004)
Due the scarcity of studies about post-harvest conservation of Macrobrachium rosenbergii and few knowledge in this topic, the aim of this work was to evaluate it shelf-life when stored as a whole in ice during 10 days. Two conditions were compared: with direct ice contact and without ice contact. In both treatments were observed an increase (P<0,05) in Non-Protein Nitrogen, Total Volatile Base Nitrogen, Thiobarbituric Acid Reactive Substances and pH values. No faecal coliforms were observed in the prawn muscles during the storage. The score of total coliforms and psychrotrophic counting that was present in the storage period didn´t exceed the law limits allowed for consumption. There was degradation in flavour and odour attributes for both treatments during the storage. Analysis of tactile and oral texture showed a fast and significant degradation in both treatments in the first days of storage, and the same occurred with the instrumental compression force tests. We concluded the Macrobrachium rosenbergii could be consumed until the 4th storage day, either if kept in direct ice contact or packed in polyethylene bags.

Sendo escassos os estudos sobre a conservação pós-captura do Macrobrachium rosenbergii e insuficientes os conhecimentos existentes, este trabalho teve como objetivo avaliar alterações na sua qualidade quando armazenado inteiro, em gelo, durante 10 dias. Foram comparadas duas condições de armazenamento: com e sem contato direto com o gelo. Em ambos os tratamentos foram observados aumentos (P<0,05) nos valores de Nitrogênio Não-Protéico, Nitrogênio de Bases Nitrogenadas Voláteis, Substâncias Reativas ao Ácido Tiobarbitúrico e pH. Não foram encontrados coliformes fecais no músculo do camarão. As contagens para coliformes totais e para bactérias psicrotróficas encontradas no período de estocagem não ultrapassaram os limites permitidos para o consumo. Foi observada perda nos atributos sabor e odor nos dois tratamentos. As análises de textura tátil e oral demonstraram diminuição rápida e significativa nos primeiros dias de estocagem, o mesmo ocorrendo com a força de compressão, medida instrumentalmente. O Macrobrachium rosenbergii manteve-se apto ao consumo até o 4º dia de armazenamento em gelo, em contato direto ou embalado em saco de polietileno.
Changes in the quality of freshwater prawn Macrobrachium rosenbergii during storage in ice
Keywords: prawn; mushiness; deterioration; shef life; Macrobrachium rosenbergii; camarão; mushiness; deterioração; vida-útil; Macrobrachium rosenbergi